The effect of solids residence time on phosphorus adsorption to hydrous ferric oxide floc. (1st November 2015) - Conidi, Daniela; Parker, Wayne J.
Abstract: The impact of solids residence time (SRT) on phosphate adsorption to hydrous ferric oxide (HFO) floc when striving for ultra-low P concentrations was characterized and an equilibrium model that describes the adsorption of P onto HFO floc of different ages was developed. The results showed that fresh HFO had a higher adsorption capacity in comparison to aged (2.8, 7.4, 10.8 and 22.8 days) HFO and contributed substantially to P removal at steady state. P adsorption onto HFO solids was determined to be best described by the Freundlich isotherm. P desorption from HFO solids was negligible supporting the hypothesis that chemisorption is the mechanism of P adsorption on HFO solids. A model that included the contribution of different classes of HFO solids (i.e. High, Low or Old, containing high concentration, low concentration or no active surface sites, respectively) to adsorption onto HFO from a sequencing batch reactor (SBR) system was found to adequately describe P adsorption onto HFO solids of different ages. From the model it was determined that the fractions of High and Low HFO decreased with SRT while the fraction of Old HFO increased with SRT. The transformation of High HFO to Low HFO did not limit the overall production of Old HFO and the fresh HFO solids contributed more to P removal at steady state than the aged solids. Graphical abstract: Highlights: The impact of SRT on phosphate adsorption to HFO floc was characterized. A model describing the sorption of P onto HFO floc of different ages was developed. Fresh HFO have a higher sorption capacity than aged (2.8–22.8 days) HFO. Fresh HFO contributed more to P removal at steady state. Adsorption was best described with the Freundlich isotherm.